The disagreement issue in the judiciary based on witness and oath (Comparative jurisprudential study) (Journal of Imam Al-Kadhim College, 2023)
Abstract : (Inferring the dispute in the judiciary by witnessing with the oath through inductive jurisprudence)     How to resolve the dispute between scholars: (in judging by witness with an oath)      If the judge wants to rule on a case, then he must rely on the evidence of the plaintiff, which is two just witnesses. The plaintiff's evidence is complete and he did not ask for the defendant's oath. In this case, can the judge pass a witness for him with the defendant's oath? or not ? Here it is necessary to be in detail: with regard to the limits, there is no saying of the scholars to hear the claim abstracted from the complete evidence. As for other than the limits, there are two sayings among the scholars:First: Those who deny permissibility, and they are a group of scholars from among the common people, and they infer verses from the Noble Qur’an and prophetic hadiths.Second: Those who say that it is permissible, and they are the Imamiyya and a group with them from among the scholars from among the common people. Often  .
Keywords: disagreement, witness and oath, comparative jurisprudential